Cytoplasmic FMRP interacting protein 1/2 (CYFIP1/2) expression analysis in autism - Noroozi, Rezvan; Omrani, Mir Davood; Sayad, Arezou; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Metabolic brain disease, 2018)
Cytoplasmic FMRP interacting proteins 1 and 2 (CYFIP1/2) have been previously shown to be associated with central nervous system (CNS) disorders such as autism spectrum disorder (ASD). Moreover, dysregulation of their expression levels results in disturbances in CNS maturation and neuronal interconnections. In the present study, we compared expression levels of CYFIP1/2 in peripheral blood of 30 ASD patients and 41 healthy subjects by means of real time PCR. Expression analysis showed significant over-expression of CYFIP1 /2 in ASD patients compared with healthy subjects (Fold change = 3.252, P < 0.0001 and Fold change = 4.14, P = 0.001 respectively). Such over-expression was also seen for CYFIP1 in male and female patients when compared with the corresponding control subjects. In addition, a significant correlation was found between CYFIP1 transcript levels and age in female subjects. A significant correlation was detected between expression levels of these genes in control subjects. The current study provides further supports for contribution of CYFIP1/2 in the pathogenesis of ASD and potentiates it as a peripheral marker for ASD diagnosis. Future studies in larger sample sizes are needed to confirm the results of the current study.